A meta-analysis of combined generic-covered stent-graft with or without bare-metal stent for refractory variceal bleeding - Hongcheng Ren; Mingchao Ding; Xiaoyong Huang; Bin Wang; Guoqing Chi; Changgang Shao; Shiyong Song; Wenjie Song; Ruina Shi (Journal of Minimal Access Surgery, 2022)
Objectives: The meta-analysis was conducted to systematically assess the efficacy and safety of generic stent-graft/bare-stent combination compared with Fluency stent alone in transjugular intrahepatic portosystemic shunt procedure for refractory variceal bleeding. Methods: PubMed, EMBASE, Scopus, Web of Science and the Cochrane Database were searched for relevant studies from January 1990 to September 2020; outcome measures studied were primary patency, hepatic encephalopathy, survival, re-bleeding and portal venous pressure. Results: Four studies (1 randomised controlled trial and 3 retrospective studies) with 449 subjects (157 patients in the combined stent group and 292 patients in the covered stent group) were included. No significant difference was observed in the incidence of mortality (hazard ratio [HR] = 1.069, 95% confidence interval [CI] [0.524, 2.178]), hepatic encephalopathy (odds ratio [OR] = 0.860, 95% CI [0.341, 2.169], P = 0.750) and re-bleeding (OR = 1.049, 95% CI [0.226, 4.881], P = 0.951). Compared with Fluency stent alone, combination therapy was associated with moderate decrease in outcomes on the post-operative portal venous pressure (standard mean difference [SMD] −0.210, 95% CI [−0.418, −0.001], P = 0.049) and was not associated with significant decrease in outcomes on the pre-operative portal venous pressure (SMD − 0.129, 95% CI [−0.336, 0.078], P = 0.223). The primary patency was significantly lower in the Fluency/bare-stent combination group (HR = 0.473, 95% CI [0.288, 0.776]). Conclusions: Generic stent-graft/bare-stent combination therapy was associated with significantly lower primary patency compared to Fluency stent alone.